Board Characteristics and Stock Price Crash Risk: The Mediating Role of Audit Committees Effectiveness - Rawad Kareem Salloomi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Stock price crash risk has become a critical concern in investment decision making and risk management, drawing the attention of investors and regulators amid a dynamic global business environment and repeated financial crises. However, empirical evidence on this issue remains limited in developing countries, particularly in the Iraqi context. Therefore, this study examines the relationship between board characteristics—board gender diversity, board size, and board independence—and stock price crash risk, as well as the mediating role of audit committee effectiveness. The study uses secondary data from ten banks listed on the Iraq Stock Exchange (ISX) during the 2017–2023 period. The findings show that board gender diversity and board size significantly reduce stock price crash risk. Higher female representation on boards is associated with more conservative decision making and stronger monitoring, which improves financial reporting transparency. An appropriately sized board also enhances oversight and lowers the likelihood of extreme negative stock price movements. In addition, the results indicate that the frequency of audit committee meetings mediates the relationship between board independence and stock price crash risk, suggesting that board independence is more effective when supported by an active audit committee. This study recommends that investors and financial analysts consider board characteristics and audit committee effectiveness when assessing firm value and risk. Furthermore, regulators and policymakers are encouraged to promote gender diversity on corporate boards to strengthen governance quality and reduce the probability of stock price crashes.